An Investigation into Conventional Spinning Process Using Ball Shaped Rollers as Forming Tool - Abd-Eltwab, Ayman Ali; Helal, Gamal I.; El-Sheikh, Mohamed N.; Saied, Essam Khalaf; Atia, Ahmed M. (Manufacturing Technology Journal, 2023)
Conventional spinning is one of the oldest processes used widely in manufacturing to obtain cup shape products. Conventional spinning is the technique that produce axisymmetric part or component over rotating mandrel with the help of rigid tool known as rollers. The shape of roller is very important parameter for the success of the spinning process. This paper datils about using ball shaped rollers as forming tool in conventional spinning process experimentally. The experimental work was carried out on the center lathe machine as forming machine, the spinning tool or spinning rollers was installed on a dynamometer replaced the tool post while the mandrel was mounted on the lathe chuck. The spinning tool in this work consists of three rollers performing the conventional spinning. The set of rollers is mounted on jaws of lathe chuck which working as a holder for the spinning tool parts. The experimental work was conducted in order to test the proposed tool and investigate the influence of the main conventional spinning parameters (mandrel rotational speed, axial feed and blank diameter or spinning ratio) on the process forming load and the product quality. The response of the product quality and required load to process parameters such as rotational speed (76,150, 230 and 305 rpm), axial feed (0.08, 0.15,0.3, and 0.6 mm/rev) also examined new rollers in different mandrel diameters 45, 60 and 80 mm. The experimental results showed that, the suggested tool acquired a spinning ratio of 2.17 which is about 35% greater than the announced conventional spinning ratio of 1.6 without any addition to the tool just using the suggested Ball shaped roller arrangement. the mandrel rotational speed, and axial feed rate are the most pronounced parameters, which have great effects on the forming loads during the spinning process.
Keywords: Conventional spinning; Ball shaped rollers; Spinning tool; Mathematical model; Forming load; Spinning ratio